Hernioplasty of large and giant diaphragmal hernias with polypropylene and biocarbonic implant - I. I. Rosenfeld (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Aim. Highlighting the immediate and long-term results of using a biocarbon implant in comparison with the standard method of using a polypropylene implant when operating on patients with large and giant diaphragmatic hernias.Materials and methods. All patients were divided into 2 study groups, which underwent alloplasty with various implants: Group I of 221 patients who underwent alloplasty with a polypropylene mesh implant (171 patients with large hernias with an area of 10–20 cm2 and 50 patients with giant hiatal hernias with the area of the hernial defect is more than 20 cm2); Group II of 79 patients who underwent original alloplasty with a two-layer biocarbon mesh implant (50 patients with large hernias and 29 patients with giant hiatal hernias). Postoperative complications were classified according to the Clavien-Dindo scale. The De Meester Index was used as a comparison criterion.Results. The results of surgical treatment are pilot and representative, which determine the further tactics and direction of improving operations to remove large and giant diaphragmatic hernias. The data on the use of a two-layer biocarbon implant and a comparison with a polypropylene implant during onlay repair of large and giant diaphragmatic hernias are presented.Conclusion. There were significant differences in relapses of all types in favor of a biocarbon implant (5,6 versus 22,8%; p < 0,0001; Fisher's exact test).